2021
DOI: 10.1016/j.scs.2021.103222
|View full text |Cite
|
Sign up to set email alerts
|

Is compulsory home quarantine less effective than centralized quarantine in controlling the COVID-19 outbreak? Evidence from Hong Kong

Abstract: Faced with the global spread of COVID-19, the Hong Kong government imposed compulsory home quarantine on all overseas arrivals, while cities in mainland China and Macau adopted a more stringent centralized quarantine approach. This study evaluates the effectiveness of compulsory home quarantine as a means of pandemic control. Combining epidemiological data with traditional socioeconomic and meteorological data from over 250 cities, we employ the Synthetic Control Method (SCM) to construct a counterfactual “syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 80 publications
1
22
0
Order By: Relevance
“…Hence, their findings are generally consistent with our reported results that X-16 (COVID-STRINGENCY-INDEX) (1 of our top 3 control measures) is expected to be best minimize the reported G-rates across all clusters of countries from the previous country-scale analysis. The effectiveness of X-12 (PUBLIC-GATHERING-RULES) to control the G-rate parameter also aligned with the recent reported studies by Das et al (2021) and Zhu and Tan (2021) where the authors highlighted that the level of spatial interactions among individuals, in the forms of home quarantines and level of living conditions, significantly affect the spread of COVID-19, especially in urbanized cities. Overall, there is a good level of confidence that the recommended control measures of (1) X-4 (COVID-CONTACT-TRACING), (2) X-12 (PUBLIC-GATHERING-RULES), and (3) X-16 (COVID-STRINGENCY-INDEX), can be both conservative and effective to control the spread of COVID-19 in the foreseeable future, and its subsequent death rates (D-rates), while not severely compromising one nation's economic stability.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Hence, their findings are generally consistent with our reported results that X-16 (COVID-STRINGENCY-INDEX) (1 of our top 3 control measures) is expected to be best minimize the reported G-rates across all clusters of countries from the previous country-scale analysis. The effectiveness of X-12 (PUBLIC-GATHERING-RULES) to control the G-rate parameter also aligned with the recent reported studies by Das et al (2021) and Zhu and Tan (2021) where the authors highlighted that the level of spatial interactions among individuals, in the forms of home quarantines and level of living conditions, significantly affect the spread of COVID-19, especially in urbanized cities. Overall, there is a good level of confidence that the recommended control measures of (1) X-4 (COVID-CONTACT-TRACING), (2) X-12 (PUBLIC-GATHERING-RULES), and (3) X-16 (COVID-STRINGENCY-INDEX), can be both conservative and effective to control the spread of COVID-19 in the foreseeable future, and its subsequent death rates (D-rates), while not severely compromising one nation's economic stability.…”
Section: Resultssupporting
confidence: 76%
“…Chen et al (2021) exploited city-level data from China using multiple linear regression models to report that healthcare infrastructure adequacy and urban governance capacity are the optimal factors which can maximize the nation's resilience towards the current pandemic situation. For the case of Hong Kong, Zhu and Tan (2021) combined epidemiological data with relevant socioeconomic and meteorological data from over 250 cities to examine the effectiveness of home quarantines where the authors reported that the control measure can be as useful as centralized quarantine, while balancing public protection, individual freedom, and general resources. In the European continent, Sannigrahi et al (2020) extensively investigated the global and local spatial association between key socio-demographic variables and the growth and death rates due to COVID-19 in 31 different European countries by documenting that poverty and income can best minimize both COVID-19 related conditions in the European region.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, a counterfactual trend is created after considering the time trends and the demographic and geographic disparities; it is then compared with the actual trend to evaluate the effectiveness of the policy. Some policies under the COVID-19 pandemic, such as the implementation of lockdowns, use of face masks, compulsory home quarantining, and mandatory COVID-19 vaccination certificates, have been evaluated using the SCM [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in China, low-risk, medium-risk and high-risk regions represent the country's different epidemic states. Even in the same city, there may be several areas with different levels of risk, where the open requirements of indoor environments and people's activities are distinct [54] . Since the priority for medium and high-risk areas is to suppress any outbreak quickly, and to minimize the number of people infected as far as possible, the goal is not confined to restricting R 0 <=1, but to get R 0 as low as possible, while paying less attention to energy consumption.…”
Section: Discussionmentioning
confidence: 99%